Pendampingan Strategi Pemasaran Produk Minuman Juice Float Cream di Kawasan Kota - Lestari, Tri; Irwanto, Tito; Susena, Karona Cahya; Handayani, Sri; Sari, Desti Rupita (LPPM Universitas Dehasen Bengkulu, 2024)
In a country, the economy depends on the efforts made by its people. Micro, Small and Medium Enterprises (MSMEs) are businesses that have an important role in Indonesia's economic growth. One of the MSME sectors that is often found in urban areas is MSMEs in the beverage sector. This community service (PKM) activity was carried out with the MSME partner Juice Float Cream in the city area. In this activity the aim is to provide motivation for MSMEs to improve marketing so that they can increase income. This service activity is carried out using providing material regarding financial management and digital marketing as well as strategies that must be implemented by MSMEs. The conclusion from this service is that MSMEs need assistance in terms of product marketing assistance in both online and offline markets.